Effects of Work-Life Balance and Work Environment on Employee Engagement Among Generation Z in Private Companies - Shofiyatunnisa, Firny (Journal Research of Social Science, Economics, and Management, 2025)
The entry of Generation Z into the world of work brings new dynamics and expectations, especially regarding work-life balance and a conducive work environment. This phenomenon creates its own challenges for private companies in maintaining and increasing employee engagement. This study aims to analyze the influence of work-life balance and work environment on employee engagement among Generation Z in private companies. The phenomenon of Generation Z entering the workforce has changed organizational dynamics, where this generation has different expectations regarding work-life balance and conducive work environments. This research uses a qualitative approach with phenomenological methods to understand the deep experiences of Generation Z employees. Data were collected through in-depth interviews with 15 informants who are Generation Z employees in various private companies. The results show that work-life balance and work environment have a significant influence on Generation Z employee engagement levels. Good work-life balance, which includes work time flexibility, support for personal life, and policies that support life balance, has been proven to increase employee engagement. Meanwhile, a positive work environment, including an inclusive organizational culture, adequate technology support, and good interpersonal relationships, also contributes to increased employee engagement. These findings provide practical implications for companies in designing effective human resource management strategies to optimize Generation Z employee engagement.